Protective factors associated with reduced substance use and depression among gender minority teens - Burstein, Dina; Purdue, Eliza Loren; Jones, Jennifer A.; Breeze, Janis L.; Chen, Ye; Sege, Robert (Journal of LGBT youth, 2024)
Gender minority (GM) students are at high risk for substance use and depression. This study explores the role of protective factors in reducing rates of substance use and depression based on high school surveys. Univariate and multivariate analyses were conducted to evaluate the association between exposures and outcomes. Youth completed surveys in 2018 (n = 16,288) and in 2021 (n = 10,792). GM students reported exposure to protective factors less frequently than their cisgender peers: good financial status (88.6% vs. 96.5% in 2018 and 95% vs. 97.8% in 2021), feeling a sense of school/community membership, (mean score 2.7 vs. 3.0 in 2018 and 2.6 vs. 3.0 in 2021) or having two or more caring adults in their life (61.5% vs. 79.7% in 2018 and 64.2% vs. 80.6% in 2021). GM youth experienced risk factors more often than their peers including bias-based bullying (mean score: 0.6 vs. 0.2 in 2018, 0.5 vs. 0.2 in 2021); peer victimization (0.5 vs. 0.2 in 2018, 0.3 vs. 0.1 in 2021), and homelessness/foster care exposure (32.8% vs. 10.8% in 2018 and 15.8% vs. 6.6% in 2021). Several factors mitigated depression and substance use among GM students. GM youth experienced these protective factors less frequently than their peers.